2018
DOI: 10.7567/jjap.57.04fd10
|View full text |Cite
|
Sign up to set email alerts
|

Ge p-channel tunneling FETs with steep phosphorus profile source junctions

Abstract: The solid-phase diffusion processes of three n-type dopants, i.e., phosphorus (P), arsenic (As), and antimony (Sb), from spin-on-glass (SOG) into Ge are compared. We show that P diffusion can realize both the highest impurity concentration (>7 ' 10 19 cm %3 ) and the steepest impurity profile (>10 nm/dec) among the cases of the three n-type dopants because the diffusion coefficient is strongly dependent on the dopant concentration. As a result, we can conclude that P is the most suitable dopant for the source … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 37 publications
(53 reference statements)
0
6
0
Order By: Relevance
“…On the other hand, various combinations of III-V, SiGe and Ge semiconductor materials as components of hetero-structure tunneling junctions have also been examined. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In particular, a hetero tunneling junction with type-II energy band alignment is promising for reducing the effective energy barrier for BTBT, leading to an exponential increase in I on .…”
mentioning
confidence: 99%
“…On the other hand, various combinations of III-V, SiGe and Ge semiconductor materials as components of hetero-structure tunneling junctions have also been examined. [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] In particular, a hetero tunneling junction with type-II energy band alignment is promising for reducing the effective energy barrier for BTBT, leading to an exponential increase in I on .…”
mentioning
confidence: 99%
“…We have demonstrated the operation of Ge p-TFETs with the source junctions formed by P solid phase diffusion from SOG [24]. Fig.…”
Section: Strained Ultrathin-body Goi P-mosfetsmentioning
confidence: 98%
“…5 ion implantation, which can be one possible reason why there have been almost no reports on Ge p-TFETs so far. Thus, we have studied the formation of n + /p junctions by diffusion of donor impurities from Spin-on-glass (SOG) into Ge [24]. This is because we previously found that high quality p + /n junctions with steep acceptor profiles can be realized in InGaAs by Zn diffusion from SOG films [38,39].…”
Section: Strained Ultrathin-body Goi P-mosfetsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because of the importance and potential application of heavily doped epitaxial n-Ge films, it has been widely studied using various approaches. Various ex situ doping techniques such as solid-phase diffusion , or ion implantation , have been demonstrated. Our attention focused on the in situ doping approach by molecular beam epitaxy (MBE), which is potentially allowing n-type Ge layers with high doping density. , The ability to produce box-shaped dopant profiles is the advantage of the in situ doping approach over the implantation or diffusion approaches. , Despite the technological advantages of in situ doping to achieve a heavily doped Ge epilayer, the underlying mechanism of the Sb dopant distribution, which is highly susceptible to the change of deposition temperatures, has not been well studied in this in situ doping approach.…”
Section: Introductionmentioning
confidence: 99%